Combinatory effects of pineapple peel liquid organic fertilizer and rice husk charcoal on melon (Cucumis melo L.) growth and yield - Hidayat, Moh. Hamdan; Lailiyah, Wiharyanti Nur; Budi, Setyo (Jurnal Ilmiah Pertanian, 2024)
The intensive use of synthetic fertilizers in melon cultivation can reduce soil organic matter and fertility, ultimately decreasing productivity. This situation necessitates the improvement of growing media to achieve production targets through the use of rice husk charcoal and liquid organic fertilizer (LOF) from pineapple peel. This study aims to determine the combinatory effects of pineapple peel LOF and rice husk charcoal media on the growth and yield of melon plants. The research employed a factorial randomized block design (RBD) with 6 treatment levels, and data were analyzed using ANOVA followed by an HSD test at the 5% significance level. The results showed an interaction between pineapple peel POC and rice husk charcoal media on the number of leaves variable. The P0M1 treatment (positive control and 50% rice husk charcoal : 50% soil) at 52 days after planting (DAP) produced the highest number of leaves, totaling 26. However, this increase in leaf number was not accompanied by an increase in fruit weight or brix levels. These findings open opportunities for further research to understand why the increase in leaf number did not translate to higher fruit weight or Brix levels, and to identify treatment combinations that can enhance both growth and yield.